PREPARATION OF EVALUATION OF LIPID BASED NANO CARRIERS FOR DIABETIC DRUG - Harika Tummala; S. Jeganath (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Wound healing is a complex process crucial for tissue restoration and function recovery. In this study, Mupirocin-loaded liposomal hydrogels, incorporating oxidized alginate and gelatin, were developed and evaluated for wound healing applications. Liposomal hydrogels combine the advantages of liposomes, such as targeted drug delivery and stability, with hydrogels' moisture retention and ease of application on wounds.Using a 32 full factorial design, the concentrations of oxidized alginate and gelatin were varied, and critical parameters were studied, including gelling time, swelling index, water vapor transmission rate (WVTR), and in vitro drug release. Fourier-transform infrared (FT-IR) analysis confirmed the successful oxidation of sodium alginate. The optimized liposomal hydrogel displayed desirable properties, including a gelling time of 43 seconds, swelling index of 71.43%, and WVTR of 98.85 g/m2/h.In vitro release studies demonstrated sustained drug release, and SEM and XRD studies provided insights into the hydrogel's structure and amorphous state of the drug. Stability studies confirmed the hydrogel's stability over time.